Investigation of interaction of aminoethylethylenediamine with sunflower oil - Мельник, Анатолий Павлович; Чумак, Ольга Петровна; Малик, Сергей Григорьевич; Хусанов, Алишер Евадиллович (Eastern-European Journal of Enterprise Technologies, 2015)
The interaction reaction of sunflower oil with hydroxyethylethylenediamine at molar ratios of reactants of from 1: 1 to 1: 3, and temperatures of 393 K – 433 K by changes in the amine concentration over time was investigated, based on which the rate constants, activation energy and entropy were calculated. Using a kinetic first-order reaction model, the estimated thermodynamic parameters, changes in the amine concentration over time were calculated and compared with the experimental values. Analysis of variance between concentrations indicates that the amine concentration can be used for the sunflower oil amidation reaction control only at the initial stage. This is caused by the fact that both nitrogen and oxygen-containing products that also react with amine are formed in the oil amidation.